Análise de irradiação solar em um campus universitário no sul do Brasil - Martini, Laís Ehlert (2019)
This research aims to evaluate the behavior of solar irradiation by geographic information system (GIS) on the campus of the Federal University of Santa Maria, in the city of Santa Maria, south of Brazil. In order to evaluate the insertion of photovoltaic systems for distributed power generation. For this, a mapping of volumetric occupation (topography, buildings, afforestation and bus stops) of the UFSM university campus with GIS tool was developed to estimate and calculate by Solar Analyst / ArcGIS (GIS) the solar radiation levels available monthly and annually throughout the campus area. These solar irradiation data obtained by GIS were validated by comparing them with actual data measured on site by the photovoltaic solar system installed at the UFSM Polytechnic College and also with irradiation data obtained by the Radiasol2 software. Subsequently, the solar radiation values available in the coverage of the 26 bus stops were identified, extending these locations with a coverage radius of 30,00 meters, indicating priority locations and less shading resulting from the built and natural surroundings. The free areas on campus that received the highest levels of solar irradiation on the ground surface were also verified to indicate potential areas for leasing of new 100 kW and 1 MW photovoltaic solar plants. Then, it was estimated the energy generation of the bus stops and PV plants comparing with the electric energy demand in the UFSM campus, to verify their energy contribution. Thus, it is concluded that the solar irradiation values provided by Solar Analyst / ArcGIS (GIS) have reliability for application in the study. The predominance of sun block in the bus stop cover is mainly due to the tall tree vegetation, and among 26 studied points it would be advantageous to apply photovoltaic system in 13 shelters, classified in a ranking of radiation receives. And by the size of the PV plants, seven potential zones for 100 kW PV plant rental and one potential zone for 1 MW PV plant were identified. Finally, considering that UFSM's annual energy expenditure is 16.000.302,8 kWh/ year, if the 8 100 kW PV Plants were active, they would be able to supply 5,69% of this energy demand. By contrast, the 1 MW plant could save approximately 7,15% of this annual energy consumption from UFSM. Thus, this research studied the application of GIS tool as a methodology to map the urban environment and identify the levels of solar radiation received on the terrestrial surface, in order to enhance the power generation by photovoltaic technology.